THE HARMONIZING INSTITUTIONAL AUTHORITY TO DETERMINE STATE FINANCIAL LOSSES IN CORRUPTION CASES - Dian Devananda Akbar; Prija Djatmika; Nurini Aprilianda (CV. RADJA PUBLIKA, 2025)
The disharmony in authority among various institutions including the Supreme Audit Agency (BPK), the Government Internal Supervisory Apparatus (BPKP), the Corruption Eradication Commission (KPK), Inspectorates, Regional Apparatus Work Units (SKPD), Public Accountants, and Judges in calculating state financial losses in corruption crime cases has led to legal uncertainty and debates over which institution holds the legitimate authority to determine such losses. Through juridical, philosophical, and sociological analysis, this study finds that the source of disharmony lies in the ambiguous norms of the Corruption Crime Law, which does not explicitly designate a single institution authorized to determine state losses. Based on its constitutional position, this research asserts the urgency of establishing BPK as the sole institution authorized to calculate state losses, accompanied by vertical harmonization of the roles of other institutions, strengthening of BPK's institutional capacity, standardization of audit methodologies, and a reaffirmation of corruption as a serious crime requiring evidentiary certainty. This study concludes that harmonizing authorities is an urgent step to strengthen the effectiveness and integrity of corruption law enforcement while enhancing public trust in Indonesia's anti-corruption mechanisms.